2019
DOI: 10.21203/rs.2.13516/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of Predictability and Influence factors of the Achieved Lenticule Thickness in Small Incision Lenticule Extraction

Abstract: Background To evaluate the differences between the predicted and achieved lenticule thickness (ΔLT) after small incision lenticule extraction (SMILE) surgery and investigate relationships between ΔLT and refractive errors or lenticule depth in SMILE. Methods A total of 184 eyes from 184 consecutive patients who underwent SMILE were included in this prospective study. One eye for each patient was randomly selected and included for statistical analysis. An ultrasound pachymetry measurement and Scheimpflug cam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…Moreover, as attempted SE correction increased, more corneal stromal tissues were removed, and stronger corneal stromal expansion strength was observed. In a study evaluating the difference in CCT reduction after SMILE in various degrees of myopia, the deviations were 20.08 ± 6.84 lm and 7.20 ± 10.50 lm in the high and low myopia groups, respectively [13]. Notably, our study included eyes with myopia more than -9.0 D, and the deviation was larger than that of the former study, further supporting Reinstein et al's hypothesis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, as attempted SE correction increased, more corneal stromal tissues were removed, and stronger corneal stromal expansion strength was observed. In a study evaluating the difference in CCT reduction after SMILE in various degrees of myopia, the deviations were 20.08 ± 6.84 lm and 7.20 ± 10.50 lm in the high and low myopia groups, respectively [13]. Notably, our study included eyes with myopia more than -9.0 D, and the deviation was larger than that of the former study, further supporting Reinstein et al's hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…First, CCT reduction was overestimated at approximately 23 lm 6 months after SMILE, which was concordant with the results of previous studies. According to several previous studies, CCT reductions could be overestimated at approximately 15-18 lm when examined by Pentacam imaging and approximately 13-24 lm by optical coherence tomography (OCT) after SMILE [6,9,12,13]. Corneal remodeling pattern was hypothesized as an influencing factor causing the discrepancy between predicted and achieved CCT reductions.…”
Section: Discussionmentioning
confidence: 97%
“…A 10% refractive sphere overcorrection nomogram is commonly used by SMILE surgeons to obtain accurate outcomes. 8 This need is justified by the expected undercorrection provided by the postoperative epithelial thickening and stromal underablation after SMILE. The fact that this nomogram uses a percentage (and not a constant value) means that the higher the myopia, the higher the overcorrection needed, and so our finding correlates better with clinical practice than that reported by Reinstein.…”
Section: Discussionmentioning
confidence: 99%
“…7 In this scenario, corneal stromal changes after SMILE have attracted interest, and several authors report that preoperatively predicted lenticule thickness for SMILE significantly overestimates the postoperative real stromal change obtained, accounting for the sphere undercorrection usually seen after SMILE if no surgical nomogram is applied. [8][9][10] However, a major limitation is the fact that many of these studies use changes in axial length, Scheimpflug-based measurements (such as corneal volume or central corneal thickness), or ultrasound pachymetry to estimate this effect, which results in a misleading conclusion about the real stromal change given the secondary postoperative thickening of the central corneal epithelium occurring after any myopic laser surgery, which is not being taken into account and separately analyzed with such type of measurements. 11,12 To our knowledge , Reinstein et al are the only group that has previously attempted to separately analyze the real stromal change induced by myopic LASIK and SMILE by removing the interference caused by corneal epithelial remodeling.…”
mentioning
confidence: 99%
“…However, it is worth noting that the actual amount of tissue consumed with SMILE may be less than predicted measurements. Wu et al 35 reported a 10% overestimation of the predicted lenticule thickness measurement using nomogram and VisuMax readout in comparison with the achieved lenticule thickness. They reported that clinicians need to subtract 10% of this predicted value to find the exact residual stromal bed thickness.…”
Section: Discussionmentioning
confidence: 99%